Design And Analysis Of Piezoelectric Configuration For Raindrop Energy Harvester - Izhab, Muhammad Izrin (2018)
The past decade has been witnessed a huge growth in a renewable energy from renewable resources such as mechanical vibration, solar, wind and biomass. Based on literature review, raindrops have a huge potential as a renewable resource for a piezoelectric raindrop energy harvester (PREH) system. In this study, the PREH system with a suitable AC-DC power converter is developed. The objectives of this research are to characterise and compare different configurations of Polyvinylidene Fluoride (PVDF) piezoelectric as well as to analyse different types of AC-DC power converter performance for PREH system. NE 300 syringe pump equipment was used to produce artificial raindrops and was located at 1.3 m above the PVDF piezoelectric generator. Three different configurations of piezoelectric which are single, X-Shaped and double layer were characterised and compared to determine the best performance in the term of output power generated. Then, the best configuration of PVDF piezoelectric was utilised in the AC-DC power converter. Different circuits of AC-DC power converter which are half-wave rectifier, full-wave rectifier and voltage doubler were compared to choose the suitable AC-DC power converter for PREH system. Finally, the output voltage of the AC-DC power converter was utilised in the energy storage circuit. The results revealed that the double layer PVDF piezoelectric generated the highest AC output power (12.11 μW) with the 196.09% improvement from the single PVDF piezoelectric. Whereas, the X-Shaped PVDF piezoelectric and the single PVDF piezoelectric generated 7.72 μW and 4.09 μW respectively. Furthermore, voltage doubler was found to be an effective AC-DC power converter with the highest DC voltage of 1.49v followed by the full-wave rectifier, 1.31v. Finally, this study also found that the PREH from multiple drops at 70 ml/min with 60 ml volume of water can charge the battery from 990 mv to 995 mv within 2:26 minutes.